Zoledronic acid-encapsulating self-assembling nanoparticles and doxorubicin: a combinatorial approach to overcome simultaneously chemoresistance and immunoresistance in breast tumors (2016)
The resistance to chemotherapy and the tumor escape from host immunosurveillance are the main causes of the failure of anthracycline-based regimens in breast cancer, where an effective chemo-immunosensitizing strategy is lacking. The clinically used aminobisphosphonate zoledronic acid (ZA) reverses chemoresistance and immunoresistance in vitro. Previously we developed a nanoparticle-based zoledronic acid-containing formulation (NZ) that allowed a higher intratumor delivery of the drug compared with free ZA in vivo. We tested its efficacy in combination with doxorubicin in breast tumors refractory to chemotherapy and immune system recognition as a new combinatorial approach to produce chemo- and immunosensitization. NZ reduced the IC50 of doxorubicin in human and murine chemoresistant breast cancer cells and restored the doxorubicin efficacy against chemo-immunoresistant tumors implanted in immunocompetent mice. By reducing the metabolic flux through the mevalonate pathway, NZ lowered the activity of Ras/ERK1/2/HIF-1? axis and the expression of P-glycoprotein, decreased the glycolysis and the mitochondrial respiratory chain, induced a cytochrome c/caspase 9/caspase 3-dependent apoptosis, thus restoring the direct cytotoxic effects of doxorubicin on tumor cell. Moreover, NZ restored the doxorubicin-induced immunogenic cell death and reversed the tumorinduced immunosuppression due to the production of kynurenine, by inhibiting the STAT3/indoleamine 2,3 dioxygenase axis. These events increased the number of dendritic cells and decreased the number of immunosuppressive T-regulatory cells infiltrating the tumors. Our work proposes the use of nanoparticle encapsulating zoledronic acid as an effective tool overcoming at the same time chemoresistance and immunoresistance in breast tumors, thanks to the effects exerted on tumor cell and tumor-infiltrating immune cells.